2011
DOI: 10.2135/cropsci2011.01.0034
|View full text |Cite
|
Sign up to set email alerts
|

A Growing Degree Day Model to Schedule Trinexapac‐ethyl Applications on Agrostis stolonifera Golf Putting Greens

Abstract: Trinexapac-ethyl (TE) is a widely used growth regulator in the turfgrass industry. Poor summer efficacy has been related to more rapid metabolism in the plant. The purpose of this study was to determine if a growing degree day (GDD) model could be used to identify the optimum TE reapplication interval for putting greens. This objective was accomplished through model development and validation. Model development was conducted on a creeping bentgrass {Agrostis stolonifera L.) golf putting green in Madison, Wl, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 33 publications
5
62
0
Order By: Relevance
“…Knowledge of the cumulative GDD to reach peak suppression was important to determine application intervals of PGRs that maximize growth suppression and minimize rebound growth (Kreuser and Soldat, 2011). Kreuser and Soldat (2011) suggested that PGRs are to be reapplied at 1.3× the GDD value at peak suppression to minimize rebound growth and maximize PGR benefits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowledge of the cumulative GDD to reach peak suppression was important to determine application intervals of PGRs that maximize growth suppression and minimize rebound growth (Kreuser and Soldat, 2011). Kreuser and Soldat (2011) suggested that PGRs are to be reapplied at 1.3× the GDD value at peak suppression to minimize rebound growth and maximize PGR benefits.…”
Section: Resultsmentioning
confidence: 99%
“…The methods for development of a GDD model for TE applications on bermudagrass putting greens were similar to those outlined by Kreuser and Soldat (2011) and Kreuser et al (2017). Experiments were conducted June to October 2017 on three ultradwarf hybrid bermudagrass cultivars at three separate locations in the southeastern Untied States: MiniVerde at the East Tennessee Research and Education Center in Knoxville, TN; Champion at the Hope Valley Country Club in Durham, NC; and TifEagle at the R.R.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A split application of a GRP generally results in a positive TSW and SV response to N rate while plots treated with a single application of a GRP demonstrated a negative TSW and SV response to N rate (Table 7). Split applications of a GRP may be more effective at providing season long vegetative growth suppression than single applications at higher rates (Kreuser and Soldat, 2011), which could potentially result in higher quality seed in a seed production field. Previous studies have shown that GA inhibitors can increase WSC within grass plants following application so the positive TSW and SV response to N rate could be due to a combination of increased WSC production and WSC transport during seed fill as a result of greater efficacy of the split GRP application (Han et al, 2004, Rolston et al, 2010b.…”
Section: Discussionmentioning
confidence: 99%